Estudo do papel do receptor ativado por protease 2 no recrutamento de leucócitos e na produção de mediadores inflamatórios em modelo experimental de asma induzido por ovalbumina em camundongos - Natália Alves de Matos (2017)
Proteinase-activated receptors (PAR) are part of a family of G-protein-coupled receptors that are activated via proteolytic cleavage of a specific sequence of amino acids in N-terminal portion, and their activation has been implicated in the regulation of inflammation. PAR-2 has been implicated in mediating allergic airway inflammation once is expressed by many cells in the airways as well as in epithelial and alveolar macrophages. The aim of this study was to study the role of PAR-2 activation in the production of inflammatory mediators and on the recruitment of leukocytes in experimental ovalbumin (OVA)-induced asthma models. All experimental protocols were approved by local UFMG Ethics’s Committee for Animal Use - certificate number 348/2014. Allergic lung inflammation was induced in sensitized BALB/c mice (female, 8-10 weeks) through the intranasal instillation of ovalbumin (OVA, 10μg) in two distinct experimental models differing in relation to the number of intranasal challenges (3 or 6 challenges). Bronchoalveolar lavage (BAL) was performed and lungs were obtained in different intervals of time, from 30 min to 72 h after challenging. To evaluate the participation of PAR-2 in experimental asthma, sensitized mice were pretreated with selective PAR-2 antagonist (ENMD1068, 0.1-1.0 mg / kg, intraperitoneal) 1 hour before intranasal instillation of OVA. The blockade of the action of PAR-2 activating endogenous proteases in PAR-2 antagonist-treated mice, played an important role on the control of allergic respiratory inflammation in both asthma’s models. Overall, pretreatment with PAR-2 antagonist ENMD1068 inhibited the recruitment of neutrophils, eosinophils, mononuclear cells to LBA when compared to OVA-treated mice. After OVA instillation (3 intranasal challenge model), PAR-2 blockade reduced PAR-2 protein expression in leukocytes, CXCL1, IL-6 and CCL5 production in BAL and IL-1β releasing into the lung, vascular permeability in lung and M2 lung macrophages population. In addition, PAR-2 blockade increased IL-10 levels in BAL when compared to OVA group. Six intranasal challenge model also promotes leukocyte infiltrating into BAL in a PAR2-dependent manner. PAR-2 blockade impairs eosinophil peroxidase (EPO) and myeloperoxidase (MPO) activity at the parenchyma lung, proteins extravasation into BAL, reduces the loss of dynamic pulmonary compliance and the lung resistance in response to methacholine, as well as mucus production and collagen deposition when compared to OVA-challenged. In the present study we demonstrated a role for PAR-2 activation in the modulation of essential phenomena leading to allergic asthma in BALB/c mice both models. In addition, the blockade of the action of PAR-2 activating endogenous proteases in PAR-2 antagonist-treated mice played an important role on the control of allergic respiratory inflammation, suggesting that PAR-2 blockade may be useful as a new pharmacological approach regarding the treatment of airways allergic diseases.